1998
DOI: 10.1097/00001756-199807130-00048
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrone, a novel anticonvulsant agent? Insights from three experimental epilepsy models

Abstract: Dipyrone, a non-steroidal anti-inflammatory agent, was anticonvulsant in three experimental epilepsy models. At a dose of 300 mg/kg i.p., dipyrone blocked the maximal hind limb extension in the electroshock model in Wistar rats, the tonic-clonic component of acute sound-induced seizures and the limbic component of audiogenic kindling in genetically susceptible Wistar-derived rats, all in 100% of the animals. In the electroshock model higher doses (400 and 500 mg/kg) were also effective but lower doses (100 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…Different hypotheses to explain this effect have been proposed, such as the inhibition of prostaglandin production, blockade of the inactivation of adenosine (a potent inhibitory neuromodulator), activation of GABA A receptors, and an antiglutamatergic effect (32,33). Finally, an extrasynaptic presence of GABA B receptors has been proposed, although for these receptors to be activated continuously, elevated concentrations of GABA in the extracellular fluid are necessary or its concentration needs to be increased close to these receptors through the release from various neurons (4,23,34).…”
Section: Discussionmentioning
confidence: 99%
“…Different hypotheses to explain this effect have been proposed, such as the inhibition of prostaglandin production, blockade of the inactivation of adenosine (a potent inhibitory neuromodulator), activation of GABA A receptors, and an antiglutamatergic effect (32,33). Finally, an extrasynaptic presence of GABA B receptors has been proposed, although for these receptors to be activated continuously, elevated concentrations of GABA in the extracellular fluid are necessary or its concentration needs to be increased close to these receptors through the release from various neurons (4,23,34).…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed that dipyrone is also active against pentylenetetrazole seizures (Magalhaes LH, Doretto MC and Moraes MF, unpublished results). The dose of dipyrone used was that with a maximal effect and was obtained from a previously constructed dose-response curve (10).…”
Section: Discussionmentioning
confidence: 99%
“…For audiogenic seizures, genetically susceptible female animals (60-90 days old) were taken from our own colony of Wistar audiogenic rats, currently bred at the animal facilities of the Physiology and Biophysics Department at the Institute of Biological Sciences, Federal University of Minas Gerais, Brazil (10,13). In both groups, animals were housed 5 per cage and kept at 24ºC with free access to food and water under a 12-h artificial light/dark cycle.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other central effects, distinct from this analgesic effect, have been evaluated. Dipyrone has been shown to produce anticonvulsant effect in rats exposed to the audiogenic and electroshock-induced seizures [7]. Dipyrone was also found to reverse the mechanical allodynia induced by CFA, and reduce the immobility time in tail suspension test in a study that compares the depression-like behavior of analgesics and bupropion in a model of chronic inflammation-related depression in mice [8].…”
mentioning
confidence: 97%